Multi-purpose portable pulley / Muhammad Arif Akmal Mohd Alias ...[et al.] - Mohd Alias, Muhammad Arif Akmal; Mohd Yahya, Muhammad Hazim; Mohd Faizal, Muhammad Fahmi Hakimi; Md Shah, Nurul Syahirah; Mohamad Naser, Muhammad Haziq
Lifting objects can be very hard as it requires a large amount of energy and stamina. A healthy person might be having problems and limitations when they need to climb up the stairs while carrying their objects to their home. Therefore, we design and innovate Multi-Purpose Portable Pulley that helps to solve this problem. faster. The purpose of this product is to lift objects from one place or floor to another without using much energy and save time as the loads can be carried easily at one go and faster. The user’s only need to install the pulley at their balcony or any suitable spots and lift the load by rotating the crank handle. This product is designed to be light, compact, portable and user’s friendly to make lifting easier and more efficient. Various methods such as concept designing, calculation analysis, engineering was performed to innovate our product. For each concept design, we have justified and compared the pros and cons of each of the design selection. Besides, 3D simulation, analysis and survey were also executed to find the best criteria and design which meet the safety requirements and practicality. In the analysis, our Multipurpose Portable Pulley operated very well without any failure due to proper choice of design, suitable material, and the fabrication methods. Hopefully, this design can be helpful to solve the lifting problems by the society.